Anti-tumor activity of PI3K-δ inhibitor in hematologic malignant cells: Shedding new light on resistance to Idelalisib. (April 2017) - Bashash, Davood; Safaroghli-Azar, Ava; Dadashi, Maryam; Safa, Majid; Momeny, Majid; Ghaffari, Seyed H.
Abstract: Genetic and laboratory experiments have brought remarkable advances in management of human malignancies, which not only revolutionized the understanding of the disease, but also led to development of novel and effective targeted therapies against specific deregulated pathways. This study aimed to investigate anti-cancer effects of Idelalisib, a potent PI3K-δ inhibitor, in a panel of hematological cell lines. The resulting data showed that Idelalisib decreased cell survival in all the tested cell lines; however, as compared to NB4, viability of other cell lines, irrespective of their molecular characteristics or even the compensatory activation of MEK/ERK pathway, was inhibited at higher concentrations. This study suggests for the first time that there is a significant correlation between relative response to Idelalisib and basal expression levels of anti-apoptotic genes, in particular survivin and MCL-1. Intriguingly, we found that Idelalisib-induced apoptosis in NB4, as the most sensitive cell line with the lowest expression level of the aforementioned genes, is executed probably via alteration in the transcriptional level of apoptosis-related genes coupled with p21-mediated caspase-3 activation. Moreover, the lower concentrations of Idelalisib combined with arsenic trioxide (ATO) produced synergistic anti-cancer effect in APL-derived NB4 cells. Overall, due to the pharmacologic safety of Idelalisib and its broad clinical effectiveness in chronic lymphoproliferative disorders, our study suggests that this inhibitor is a promising agent for the treatment of acute promyelocytic leukemia, either as single agent or in a combined-modality strategy.